Acute toxicity test ethanol extract of kerehau leaf (Callicarpa longifolia Lamk) using OECD 420 method - Aulia Nurfazri Istiqomah; Shintya Safitri; Elis Susilawati (Jurnal Ilmiah Farmasi, 2020)
AbstractBackground: Kerehau is empirically used as cooling powder to treat acne. Based on previous research, kerehau leaves have a number of activities, including wound healing, antidiabetic, and anti-inflammatory.Objectives: This study aimed to determine the safety level of a single dose of ethanol extract of kerehau leaves within a 24-hour administration period.Methods: Acute toxicity testing of ethanol extract of kerehau leaves was carried out on female Webster mice. Test animals were divided into 4 treatment groups, consisting of 1 control group and 3 test groups. The testing method referred to OECD (Organization of Economic Cooperation and Development) 420 with modified doses of 2000mg/kgBW, 5000 mg/kgBW, and 8000 mg/kgBW. The observations were made on the behaviour of animals towards toxicity symptoms for 4 hours after administration of the test substance as well as death. The death and weight gain were observed for 14 days. On the 15th day, animals were sacrificed, blood was taken, and biochemical parameters were measured. The heart, kidneys, liver, spleen, and lungs were harvested and weighed. Data was analysed using Oneway ANOVA continued with LSD and Post Hoc.Results: The results showed that ethanol extract of kerehau leaves did not cause death in all of the groups. There were significant differences in liver weight, SGPT, and SGOT levels (p< 0.05) at the dose of 5000 mg/kgBW. No toxicity symptoms and death were found until the end of the experiment.Conclusion: LD50 value of ethanol extract of kerehau leaves was above 8000 mg/kgBW with heart as the most affected organ.Keywords: Ethanol extract of kerehau leaves, acute toxicity test, OECD 420.Latar Belakang : Beragam  khasiat yang dimiliki daun kerehau menjadi dasar dilakukannya uji toksisitas akut untuk mengetahui adanya potensi toksik dan organ sasaran yang dipengaruhi.Metode : Metode pengujian toksisitas akut diadaptasi dari OECD 420 dengan dosis 2000 mg/kgbb, 5000 mg/kgbb dan 8000mg/kgbb. Pengamatan dilakukan  terhadap gejala toksik yang muncul, kematian dan berat badan. Pada hari ke-15 dilakukan pengukuran SGPT, SGOT , kreatinin dalam darah, indeks organ jantung, ginjal, hati, limpa dan paru-paru serta histopatologi organ hati dan ginjal.Hasil : Hasil penelitian menunjukkan ekstrak etanol daun kerehau mempengaruhi organ hati secara bermakna namun tidak menyebabkan kematian hingga dosis 8000mg/kgbb.Kata kunci : Ekstrak etanol, daun kerehau, toksisitas akut, OECD 420.